**Unformatted text preview: **23.25: a) b) - kq( x + a ) kq 2kq - = . x x-a x( x - a ) kq(3x - a ) kq 2kq 0 < x < a :V = - = . x a-x x( x - a) - kq kq( x + a ) 2kq x < 0 :V = + = . x x-a x( x - a) x > a :V =
2q | x - a| q Note: This can be also be written as V = k ( | x| - c)The potential is zero at x = - a and a / 3. ) d) - kqx - kq = , which is the same as the potential of a point charge x x2 q. (Note: The two charges must be added with the correct sign.) e)For x >> a : V ...

View
Full
Document